Hybrid Shifts, Leadership Lifts: How Change Leadership Can Make a Difference in Employees’ Change-Supportive Behavior During the Transition to Hybrid Working Models Since COVID-19 - Cowden, Christin Helen; Zaar, Sonja (Journal of Organizational Psychology, 2024)
The transition to hybrid working models since COVID-19 has posed significant challenges for organizations, particularly in securing employees’ support. This study investigates how change leadership shapes the latter, focusing on the interplay with leader-member exchange (LMX) and organizational identification. Using data from 282 knowledge workers across industries and ordinary least squares regression, we show a positive relationship between change leadership and change-supportive behavior mediated by LMX. Surprisingly, organizational identification negatively moderates this relationship, revealing a 'ceiling effect' where highly identified employees' intrinsic motivation diminishes the impact of change leadership. These findings provide valuable guidance for the navigation of effective change.